Continuous physiological signal measurement over 24-hour periods to assess the impact of work-related stress and workplace violence. (April 2023) - Hamidi Shishavan, Hossein; Garza, Jennifer; Henning, Robert; Cherniack, Martin; Hirabayashi, Liane; Scott, Erika; Kim, Insoo
Abstract: Work-related stress has long been recognized as an essential factor affecting employees' health and wellbeing. Repeated exposure to acute occupational stressors puts workers at high risk for depression, obesity, hypertension, and early death. Assessment of the effects of acute stress on workers' wellbeing usually relies on subjective self-reports, questionnaires, or measuring biometric and biochemical markers in long-cycle time intervals. This study aimed to develop and validate the use of a multiparameter wearable armband for continuous non-invasive monitoring of physiological states. Two worker populations were monitored 24 h/day: six loggers for one day and six ICU nurses working 12-hr shifts for one week. Stress responses in nurses were highly correlated with changes in heart rate variability (HRV) and pulse transit time (PTT). A rise in the low-to high-frequency (LF/LH) ratio in HRV was also coincident with stress responses. HRV on workdays decreased compared to non-work days, and PTT also exhibited a persistent decrease reflecting increased blood pressure. Compared to loggers, nurses were involved in high-intensity work activities 45% more often but were less active on non-work days. The wearable technology was well accepted by all worker participants and yielded high signal quality, critical factors for long-term non-invasive occupational health monitoring. Highlights: Multimodal wearable armband for non-invasive 24-hr physiological worker monitoring. Continuous measurement of Pulse Transit Time (PTT) for cuffless blood pressure. PTT and heart rate variability (HRV) used together as a biomarker of the stress response. PTT reflects a longer period of stress recovery compared to HRV. Armband useability shown in two work sectors with varied environmental conditions.